2011
DOI: 10.1007/s00442-011-2003-3
|View full text |Cite
|
Sign up to set email alerts
|

Species traits predict assembly of mayfly and stonefly communities along pH gradients

Abstract: Much recent ecological research has centred on the interrelations between species diversity and ecological processes. In the present study, I show how species traits may aid in comprehending ecology by studying the link between an environmental variable and functional traits. I examined the composition of species traits with a theoretically underpinned relationship to ecological processes along a pH gradient. I focused on body size, reproductive output, life cycle length and feeding habit of mayflies and stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…Similar to the previously investigated freshwater systems of the Dinaric Karst (Vilenica et al, 2016b), water temperature and pH were amongst the most important variables that determined mayfly assemblages and their distribution (e.g. Gerhardt, 1990;Moog, 2002;Petrin, 2011;Bauernfeind and Soldán, 2012). In addition, habitat type (springs, upper lotic habitats, tufa barriers and lower lotic habitats) and ammonium concentrations also played an important role.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to the previously investigated freshwater systems of the Dinaric Karst (Vilenica et al, 2016b), water temperature and pH were amongst the most important variables that determined mayfly assemblages and their distribution (e.g. Gerhardt, 1990;Moog, 2002;Petrin, 2011;Bauernfeind and Soldán, 2012). In addition, habitat type (springs, upper lotic habitats, tufa barriers and lower lotic habitats) and ammonium concentrations also played an important role.…”
Section: Discussionsupporting
confidence: 72%
“…Majority of mayfly species inhabit freshwaters with a neutral to alkaline pH, whereas they are highly sensitive to low pH values (e.g. Gerhardt, 1990;Petrin, 2011). pH values of the karst streams and rivers usually range from 6.5 to 8.5, due to the geological effects of karst substrate (Štambuk-Giljanović, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As water temperature was already recognized as one of the most important environmental factors influencing mayfly assemblages (e.g. Brittain 1979, Harper and Peckarsky 2006) and many authors showed that mayflies are very sensitive to low pH values (Fiance 1978, Gerhardt 1990, Petrin 2011), the results of this study are in accordance.…”
Section: Discussionsupporting
confidence: 88%
“…Moog 2002; Bauernfeind and Soldán 2012) and pH (e.g. Fiance 1978, Petrin 2011). Mayflies are highly sensitive to habitat alterations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Species' distributions change over time and over the course of their development. Putting species into a meaningful ecological context requires an understanding of their life history, trait-based adaptations, and physiological limits, as well as the range of biotic and abiotic conditions to which they are exposed Vaughn, 2010;Petrin, 2011;Díaz et al, 2013). Because having such thorough knowledge of species is rarely possible, conceptual constructs like FFG provide useful shortcuts for understanding species' contributions to ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%